Exploring Generation Y And Z Perspectives on Work-Life Balance - David Manafe; Maria Odriana Veronica Moi; Stefanie Noviega Bribin Burin (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – Employee well-being, both physical and mental, is crucial, as previous research has shown its impact on organizational success and goal achievement. These conditions encompass experiences, skills, emotions, and behavioural patterns and are influenced by individual characteristics, including generational differences. Aim – This research seeks to explore the state of work-life balance by examining three key dimensions: Work Interference with Personal Life (WIPL), Personal Life Interference with Work (PLIW), and Work and Personal Life Enhancement (WPLE) influence employee performance and happiness within two generational groups: Generation Y and Generation Z. Design / methodology / approach – This research applies a quantitative and explanatory approach, with questionnaires distributed to 770 respondents, including employees from government, private sectors, entrepreneurs, and other categories. The data was analyzed using PLS-SEM with SmartPLS version 4. Results and Discussion – The analysis results indicate that all three dimensions significantly influence the performance of employees in Generation Z. However, for Generation Y, only the WIPL and WPLE dimensions have a significant impact on their workplace performance. Both generations experience significant increases in happiness through WIPL and WPLE. Happiness is positive and significant effects on performance and only mediates the relationship with performance in Generation Z for PLIW negatively and for the WIPL and WPLE on performance for both generations with a stronger effects in Generation Y. Conclusion - This study concludes that work-life balance dimensions influence employee performance differently across generations, with stronger effects in Generation Y than Generation Z. These findings highlight the need for flexible work arrangements to optimize employee performance and happiness. Research implication – These findings have implications for work patterns, recruitment systems, and company policies, suggesting the need for effective and comfortable working methods tailored to employees from different generational categories. Limitations – The study’s limitations include the combination of all job categories, which may introduce bias in perceptions of dimensions, character, and performance. Additionally, cultural aspects should be considered as an external factor influencing individual behavior patterns and work methods.